ANALISIS KUALITAS DASAR TEPUNG BENGKUANG HASIL PENGERINGAN SISTEM PEMANAS GANDA - Erry Ika Rhofita (SENTIA 2016, 2016)
Yam (Pachyrrhizus erosus) widely cultivated in many regions in Indonesia, especially in West Java and Central Java. This fruits have many benefits in many sector, such as food industry, drugs indutry, beauty industri and many more sector, so it is so good for consumtion. The high water content of yam between 78 to 94%, which led to a faster damaged after harvest. Therefore we need further processing to extend the shelf life of yam, one of which is flouring. In the process of making flour yam, drying is an important process that need to be considered for determining the quality of the resulting yam flour. This study aims to determine the effect of variations in temperature and the drying time of the basic quality (yield, water content and ash content) yam flour produced. From this research it is known that the higher the drying temperature and longer drying time rendemen and ash generated will be higher, while its water level will decrease. The best treatment resulting from this research is the use of a temperature of 65° C with long drying time 7 hours, resulting in a yield of yam flour is 7.74%, water content of yam flour 4.69%, and the ash content of yam flour is 5.13%.